(3QSGdI GdYQTjIs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3GdMeO ddg hGdMeO ef HfYeg GYhd ai LejY GMhGdg Ydi cQeg GeG HYO abO SCdfi HYV ef jfJei GdiGf GPcQ dg QSGdI eTJedI Ydi MbGFb Yde GdJhMjO hgPg GdQSGdI Ydi KdGKI CUhd s
(3BNQgG (B:s
(3bO jfJ dc HNjQ ebUhO HGdbUO GdChd hHGdPGJ hGf GdT OGNd HGdYQV hGdbUO GdKGfi hEf cGf cd HbOQ hGdMeO ddg hGgH GdYbd hedge GdUhGH s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B877s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg , JQeje s
Keywords: (3GdadSaI hGdefWbs